Invasi Rusia ke Ukraina Jilid II: Agresi atau Self-Defense? - Puspita, Natalia Yeti (Universitas Negeri Malang, 2022)
This study analyzed the legal status of the invasion and the legitimacy of the Russian invasion of Ukraine based on international law. This study used a normative juridical method with a conceptual approach. The legal status of invasion in international law was stated to have violated the principle of state sovereignty and the principle of non-intervention, which threatens world peace and security as stipulated in Article 2 paragraph (1), paragraph (3), paragraph (4), and paragraph (7) of the Charter of the United Nations. The legitimacy of the Russian invasion of Ukraine based on United Nations General Assembly Resolution Number 3314 (XXIX) December 14, 1974, and Article 8 bis of the Rome Statute Amendment was more appropriately considered as part of aggression rather than self-defense. United Nations General Assembly Resolution Number 3314 (XXIX) December 14, 1974, stated that an attack could be considered aggression if it fulfilled the elements of character, gravity, and scale, which resulted in an actual violation of the United Nations Charter. Article 8 bis Amendments to the Rome Statute confirmed that aggression includes the planning, preparation, and execution by a state to direct political or military action against another state.